2016
DOI: 10.3168/jds.2015-10626
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of milk protein hydrolysate in alloxan-induced diabetic rats

Abstract: We investigated the effects of milk protein concentrate (MPC) and milk protein concentrate hydrolysate (MPCH) as antioxidant agents in rats. Six groups of healthy (non-diabetic) and type-II diabetic rats were used: (1) healthy rats (control), (2) alloxan-induced rats (diabetic control group), (3) healthy rats treated orally with MPC, (4) diabetic rats treated orally with MPC, (5) healthy rats treated orally with MPCH, and (6) diabetic rats treated orally with MPCH. We concluded that treatment with MPC or MPCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…On the other hand, there was a significant decrease of TAGs in all groups when BTMP and WPH complexes were added; A similar trend was checked in TC for all components, as TC significantly decreased ( p ≤ .05) by BTMP complexes addition ( p ≤ .05), but that change is not significant when compared to the negative control group ( p > .05). The biggest reduction of plasma TC was observed with BTMP–PHM (152.00 mg/dl) because both MP and mucilage controlled the serum cholesterol level within the HFD (Awad et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there was a significant decrease of TAGs in all groups when BTMP and WPH complexes were added; A similar trend was checked in TC for all components, as TC significantly decreased ( p ≤ .05) by BTMP complexes addition ( p ≤ .05), but that change is not significant when compared to the negative control group ( p > .05). The biggest reduction of plasma TC was observed with BTMP–PHM (152.00 mg/dl) because both MP and mucilage controlled the serum cholesterol level within the HFD (Awad et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides supplying all essential amino acids, the human body needs milk proteins (MPs) which have different biological activities (antioxidant, immunomodulatory, antimicrobial, and anticancer) (Awad et al, ; El‐Maksoud et al, ; Pins & Keenan, ). Milk proteins and their hydrolyzed products affect lipid absorption (Fekete, Givens, & Lovegrove, ).…”
Section: Introductionmentioning
confidence: 99%
“…MDA, SOD, CAT were not elevated and the slight increase on day 3 of nitrotyrosine staining (protein oxidation) was observed only in the CDs offspring of dams fed HSD when compared to the Sabra rats of dams fed RD and barely reached statistical significance. This could be explained by the antioxidant effects of milk proteins, as reported by Awad et al (2016). They found that intragastric administration of milk protein concentrates or milk protein concentrate hydrolysates improved the antioxidant defense in alloxan-induced diabetic rats, reducing the levels of TBARS in the blood and liver which were elevated in the nontreated diabetic rats (Awad et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…This could be explained by the antioxidant effects of milk proteins, as reported by Awad et al (2016). They found that intragastric administration of milk protein concentrates or milk protein concentrate hydrolysates improved the antioxidant defense in alloxan-induced diabetic rats, reducing the levels of TBARS in the blood and liver which were elevated in the nontreated diabetic rats (Awad et al, 2016). An additional explanation lies in the fact that the glucose blood levels throughout pregnancy were generally below 200 mg%, and further slowly subsided postdelivery.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation